Pembunuhan Suami oleh Istri dalam Konteks Kekerasan dalam Rumah Tangga dan Penghukuman yang Dialaminya - Susanti, Vinita (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2018)
This article discusses the experience of women accused of 'killing' their husbands, with the punishment they experienced. The type of research is feminist, with a qualitative approach. Women who commit killings against their own husbands, in criminology are said to be 'typical' crimes. In a positivist (normative) legal review, these women are said to be perpetrators of murder crimes. From a criminological point of view, the perpetrator actually shows his position as a victim of domestic violence. The crimes committed by them are gender-based crimes. The focus of this paper is about punishments given to those who do not always use the PKDRT Law, even though they are within the household sphere. This study showed the experience of wives accused of being the perpetrators of murder crimes, who were victims, which had implications for the form of punishment against them. In criminology known as victims who become perpetrators.